The Role of the medical profession and its support system in the promotion of peace and the prevention of nuclear war - Soedibjo Sardadi, Soedibjo Sardadi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1986)
In this article the author describes the present development of the war machine, and its actual and potential impact on medicine. The effects of nuclear explosion are briefly discussed and the possible roles of the medical profession is brought forth in facing the current global political situation. The ethical and moral foundation of medicine is emphasized in carrying out the professional social responsibility to preserve the comprehensive health of mankind. Key Words: prevention of nuclear war - peace studies - medical polemology - medical effects of nuclear explosion - war medicine